Enhancing the Writing Process: Integrating Applied Linguistics Learning Assessment in the Classroom - Aponte-Alequin, Hector A. (European Scientific Journal, ESJ, 2025)
This study in Applied Linguistics to the writing process addresses the challenge of assessing and improving basic writing skills among 120 incoming students at the University of Puerto Rico, Río Piedras Campus. Faced with instructor reports of significant writing deficiencies and a lack of calibrated, objective evaluation methods, the study focused on developing and implementing new assessment tools within a basic writing course. Specifically, an objective test and a calibrated rubric were designed, informed by principles of applied linguistics, to establish clear performance expectations and guide pedagogical interventions. While the assessment revealed that over 70% of students demonstrated proficiency in three key learning objectives, as measured by achieving a passing score on the test and a "Good" rating on the rubric-assessed text, the substantial instructional time required to achieve these outcomes highlighted a mismatch between student needs and the existing curriculum. This finding, informed by the applied linguistic analysis of student performance, led to a significant curricular change: the original course was restructured into two distinct subjects to provide more targeted instruction and support for developing writers.